2013
DOI: 10.1108/cdi-07-2012-0067
|View full text |Cite
|
Sign up to set email alerts
|

Too much or too little? A study of the impact of career complexity on executive adaptability

Abstract: Purpose -In today's turbulent business environment leaders must be able to adapt to rapidly changing circumstances. For this research the authors aim to focus on the issue of adaptability defined as the ability to work effectively within a variety of changing situations, and with various individuals or groups. They also aimed to examine how variables of career complexity affect development of adaptability. Design/methodology/approach -The authors draw on a unique database containing the career histories of 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
9
0
3
Order By: Relevance
“…However, our participants explained their sense of success derived from the uncertainty of the journey, rather than the certainty of reaching an outcome as the focal point of success. These findings support the growing call to address the contextual and dynamic nature of career success and extend findings that support thriving careers for those who engage in proactive career behaviour (Eby et al, 2003) or the increased ability to adapt to the turbulent environment through multiple role changes (Zhu et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…However, our participants explained their sense of success derived from the uncertainty of the journey, rather than the certainty of reaching an outcome as the focal point of success. These findings support the growing call to address the contextual and dynamic nature of career success and extend findings that support thriving careers for those who engage in proactive career behaviour (Eby et al, 2003) or the increased ability to adapt to the turbulent environment through multiple role changes (Zhu et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…Lin, 2015;Lu et al, 2016;Vanhercke et al, 2015), or on employability competencies (e.g. Van der Klink et al, 2014;Van Emmerik et al, 2012;Zhu et al, 2013), which represent two of the most dominant streams of employability literature in general. Also, some studies (e.g.…”
Section: Trending Topics In Careers Between 2012 and 2016mentioning
confidence: 99%
“…In jobs with rotation, they found, for example, greater motivation (r = 0.44; Muramatsu et al, 1982; where necessary, values are converted to correlation coefficient r for easier comparison) and labor flexibility (r = 0.57; Sawhney, 2013), decreased mental fatigue (r = −0.32, Jones and James, 2018), a lower incidence of carpal tunnel syndrome (r = −0.23; Roquelaure et al, 1997), and increased process innovation performance (r = 0.21; Pini and Santangelo, 2005). However, some studies also reported contradicting significant results for motivation (r = −0.17; Mohsan et al, 2012), employee adaptability (r = −0.41; Zhu et al, 2013), employee energy (r = −0.09; Luger et al, 2016), incidence of upper-extremity musculoskeletal disorders (r = 0.07; Roquelaure et al, 2009), and innovation performance (r = −0.11; Song et al, 2010). Thus, despite much interest in job and task rotation from a variety of disciplines and from researchers and practitioners alike, there are still questions left unanswered: Does rotation really provide the benefits that organizations expect?…”
Section: Introductionmentioning
confidence: 99%